S+/S band passively Q-switched thulium-fluoride fiber laser based on using gallium selenide saturable absorber - Ahmad, Harith; Reduan, Siti Aisyah (Elsevier, 2018)
A Q-switched thulium-fluoride fiber (TFF) laser using gallium selenide (GaSe) as a passive saturable absorber (SA) for operation in the S+/S band is demonstrated. The generated pulses can be tuned from 1454 nm to 1512 nm, giving a tuning range of 58 nm. At 1502 nm, stable Q-switching operation is obtained from a pump power of 76.2 mW and is observed until the maximum pump power of 133.6 mW is reached, with the repetition rate varying from 16.5 kHz to 33.3 kHz and having a narrowest pulse width at 2.7 µs. The highest pulse energy obtained in this work is 51.4 nJ and this is, to the knowledge of the authors, the first time that Q-switching operation in the S+/S band region is obtained from a TFF laser using a GaSe based SA.